2012
DOI: 10.1111/j.1750-3841.2011.02527.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elicitor Spray at Different Reproductive Stages on Saponin Content of Soybean

Abstract: The beneficial health effects of soybeans may be enhanced by increasing bioactive compounds including soyasaponins (ssp). The objective of this study is to elucidate the effect of elicitors sprayed on Ozark variety soybeans, on ssp content. Different concentrations of elicitors, ethyl acetate (EA) and methyl jasmonate (MJ), were sprayed at 4 different growth stages (1-bloom, 2-pod development, 3-seed development, and 4-seed maturity). Seeds were ground, defatted, ssp was extracted and identified and quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Hence, our study suggested that, for a given variety and elicitor, the concentration is an important factor for reduction of LOX2. Zhang et al while studying the effect of elicitor treatment on isoflavones also reported that, with all of the elicitors tested, concentration was a more important factor than growth stage Similarly, Eswaranandam et al reported that the overall effect of elicitor on total soy saponin content was not dependent on growth stage, however, elicitors sprayed at different growth stages showed differences among elicitors applied on soybeans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, our study suggested that, for a given variety and elicitor, the concentration is an important factor for reduction of LOX2. Zhang et al while studying the effect of elicitor treatment on isoflavones also reported that, with all of the elicitors tested, concentration was a more important factor than growth stage Similarly, Eswaranandam et al reported that the overall effect of elicitor on total soy saponin content was not dependent on growth stage, however, elicitors sprayed at different growth stages showed differences among elicitors applied on soybeans.…”
Section: Resultsmentioning
confidence: 99%
“…Biotic elicitors (having biological origin) such as methyl jasmonate (MJ), salicylic acid (SA), etc. have been reported to increase production of secondary metabolites, isoflavonoid, betalain, saponin, and glucosinolates, through various mechanisms. They are natural plant growth regulator phytohormones playing key roles in the signal interplay during biotic and abiotic stresses .…”
Section: Introductionmentioning
confidence: 99%
“…Stress-induced responses in plants are mediated by several signaling molecules, including redox molecules; Ca 2+ ; reactive oxygen species; MAP kinases; and phytohormones such as jasmonic acid (JA), salicylic acid (SA), abscisic acid (ABA), and ethylene (ETH) . Under biological stress by herbivores or pathogens, phytohormone signaling will trigger immune responses by activating changes in gene transcription to recruit antimicrobial proteins, callose proteins, secondary metabolites, or additional hormones to aid in plant defense. ,, In particular, research aimed at investigating metabolic regulation of triterpene saponin biosynthesis has focused on transcription factors upregulated via the phytohormones jasmonate (JA) ,,, and methyl jasmonate (MeJA), , although other phytohormones (SA, ETH, and ABA) can also enhance saponin yields to some degree . Having been studied in various systems (whole plants, cell culture, and root tissues), JA- and MeJA-induced synthesis of triterpene saponins has been documented in multiple legume species (Glycyrrhiza glabra, Glycyrrhiza uralensis, Medicago truncatula, Medicago sativa, and Glycine max). Specifically, MeJA-induced soyasaponin synthesis enhances soyasaponin content in soybean seeds sprayed with MeJA during seed reproductive stages, in barrel medic cell cultures (soyasapogenols B and E), , and in licorice (Glycyrrhiza glabra) cell cultures (soyasapogenols B and E, soyasaponins). , Additionally, β-amyrin synthase (βAS), a key enzyme in oleanane triterpenoid saponin synthesis, is upregulated in response to MeJA in barrel medic cell cultures and in licorice cell cultures, root nodules, and germinating seeds .…”
Section: Enhancing Soyasaponin Yields: Targeted Biosynthesismentioning
confidence: 99%
“…49 Having been studied in various systems (whole plants, cell culture, and root tissues), JA-and MeJA-induced synthesis of triterpene saponins has been documented in multiple legume species (Glycyrrhiza glabra, Glycyrrhiza uralensis, Medicago truncatula, Medicago sativa, and Glycine max). 56−61 Specifically, MeJA-induced soyasaponin synthesis enhances soyasaponin content in soybean seeds sprayed with MeJA during seed reproductive stages, 58 in barrel medic cell cultures (soyasapogenols B and E), 54,56 and in licorice (Glycyrrhiza glabra) cell cultures (soyasapogenols B and E, soyasaponins). 60,61 Additionally, βamyrin synthase (βAS), a key enzyme in oleanane triterpenoid saponin synthesis, is upregulated in response to MeJA in barrel medic cell cultures 54−56 and in licorice cell cultures, root nodules, and germinating seeds.…”
Section: Threatsmentioning
confidence: 99%
“…Flavonoid concentration was also increased by 31% and 33% after 10 μM MeJA and 100 μM SA treatments, respectively in seven day old broccoli sprouts [120]. The application of ethyl acetate 0.05 M, MJ 0.001 and 0.005 M can be used at any growth stage to increase the total saponin content of soybean variety Ozark [121]. Puthusseri et al [122] informed that foliar applications of salicylic acid (250 μM) in Coriandrum sativum L. enhanced folate levels twofold (3112.33 μg/100 g DW).…”
Section: An Approach To Sustainable Agriculture Using Elicitorsmentioning
confidence: 99%